Blister formation during graphite surface oxidation by Hummers’ method - Sinitsyna, Olga V.; Meshkov, Georgy B.; Grigorieva, Anastasija V.; Antonov, Alexander A.; Grigorieva, Inna G.; Yaminsky, Igor V. (Beilstein Journal of Nanotechnology, 2018)
Graphite oxide has a complex structure that can be modified in many ways to obtain materials for a wide range of applications. It is known that the graphite precursor has an important role in the synthesis of graphite oxide. In the present study, the basal-plane surface of highly annealed pyrolythic graphite (HAPG) was oxidized by Hummers’ method and investigated by Raman spectroscopy and atomic force microscopy. HAPG was used as a graphite precursor because its surface after cleavage contains well-ordered millimeter-sized regions. The treatment resulted in graphite intercalation by sulfuric acid and blister formation all over the surface. Surprisingly, the destruction of the sp2-lattice was not detected in the ordered regions. We suggest that the reagent diffusion under the basal plane surface occurred through the cleavage steps and dislocations with the Burgers vector parallel to the c-axis in graphite.
Keywords: atomic force microscopy (AFM); graphene; graphite intercalation compounds (GICs); graphite oxide (GO); highly annealed pyrolythic graphite (HAPG)